Justification : five views - Beilby, James K.; Eddy, Paul Rhodes (London : SPCK, 2012)
For centuries the Pauline doctrine of justification has been a classic point of interpretation and debate in Christian theology. And in recent years new facets and distinctions have shaped the debate. After an in-depth introduction, this volume focuses on five views of justification: traditional reformed, progressive reformed, new perspective, deification or theosis, and Roman Catholic.
Part one : introduction -- Justification in historical perspective -- Justification in contemporary debate -- Part two : five views of justification -- Traditional reformed view -- Progressive reformed view -- New perspective view -- Deification view -- Roman Catholic view.
Includes bibliographical references and indexes.
Keywords: Justification (Christian theology) -- History of doctrines; Aufsatzsammlung